A Garbage-Collecting Typed Assembly Language - Hawblitzel, Chris; Huang, Heng; Wittie, Lea; Chen, Juan (Association for Computing Machinery, Inc., 2007)
Typed assembly languages usually support heap allocation safely, but often rely on an external garbage collector to deallocate objects from the heap and prevent unsafe dangling pointers. Even if the external garbage collector is provably correct, verifying the safety of the interaction between TAL programs and garbage collection is nontrivial. This paper introduces a typed assembly language whose type system is expressive enough to type-check a Cheney-queue copying garbage collector, so that ordinary programs and garbage collection can co-exist and interact inside a single typed language. The only built-in types for memory are linear types describing individual memory words, so that TAL programmers can define their own object layouts, method table layouts, heap layouts, and memory management techniques.
ACM Workshop on Types in Language Design and Implementation (TLDI 07)